(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2016)
Background: Lower urinary tract symptoms suggestive of symptomatic Benign Prostatic Hyperplasia (BPH) are a very common disease in elderly men .The incidence of benign prostatic hyperplasia is age related. Objectives: To compare the efficacy and safety of Tamsulosin and Terazosin in the treatment of symptomatic Benign Prostatic Hyperplasia. Methods: This was a prospective study carried out in the Department of Urology, Chittagong Medial College Hospital, Chittagong, Bangladesh during the period of July to December 2014. Total 40 patients of 45-80 years of age were consequently selected according to inclusion criteria. After completion of baseline clinical evaluation and investigations, participants were divided into two groups, group A and group B. Group A (n=20) was given Terazosin 1mg daily for 3 days at bed time and then 2 mg daily at bed time for 2 months. Group B (n=20) was given Tamsulosin, 0.4 mg per day for 2 months. Efficacy was evaluated of each group after 2 month follow up and lastly a comparison was made between them. The parameters monitored were International Prostate Symptoms Score (IPSS) Maximum urine flow rate (Qmax) and Post Voidal Residual Volume (PVR). Tamsulosin 0.4 mg and Terazosin 2 mg once daily for 8 weeks both are effective in relieving symptoms of BPH but Tamsulosin is superior to Terazosin in improvement of total IPSS (p<0.001) and Qmax (p<0.01) PVR (p<0.01) at the end point. Results: Outcome of parameters at follow up after 2 months. Tamsulosin group showed significant improvement of IPSS (p<0.05) PVR (p<0.001) and Qmax (p<0.001) than Terazosin. The incidence of adverse events by administration of Tamsulosin was less than that by Terazosin. Conclusion: Tamsulosin appears to have more efficacy and safety than Terazosin in symptomatic BPH. Chatt Shi Hosp Med Coll J; Vol.15 (1); Jan 2016; Page 17-21